The Deep Learning Approach as an Integrative Strategy between the Merdeka Curriculum and the Muhammadiyah Education Curriculum - Muhammad Izzan Naqiba (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the deep learning approach as an integrative strategy between the Merdeka Curriculum and the Muhammadiyah Education Curriculum at SMP Muhammadiyah Program Khusus Kottabarat Surakarta. The research focuses on the planning, implementation, as well as the supporting and inhibiting factors in the application of deep learning within integrated learning practices. This study employs a descriptive qualitative approach in the form of field research, with data collected through in-depth interviews, observations, and documentation. The data were analyzed through stages of data reduction, data presentation, and conclusion drawing, supported by data triangulation. The findings indicate that the deep learning approach is capable of systematically integrating the Merdeka Curriculum and the Muhammadiyah Education Curriculum through learning planning based on four core components of deep learning, the implementation of contextual and reflective learning methods, and interdisciplinary collaboration grounded in Islamic values. Supporting factors for the implementation of deep learning include the availability of learning technologies, teachers’ quality and transformative mindsets, and a collaborative culture among teachers. In contrast, inhibiting factors include differences in teachers’ mindsets, the diversity of students’ characteristics and literacy levels, and limitations in instructional time allocation. The novelty of this study lies in the finding that deep learning functions as a pedagogical bridge that not only integrates academic achievement and Islamic character formation but also humanizes the educational process in a holistic and progressive manner.